Dioscorea alata extract as anti-cancer agent by regulating genetic mutations, apoptosis, and cell proliferation: in vitro and in silico studies - Nurul Makiyah, Sri Nabawiyati; Christina, Yuyun Ika; Ahkam, Ahmad Hafidul (Penerbit Universiti Kebangsaan Malaysia, 2023)
Dioscorea alata (DA) tubers contain some compounds of potential anti-cancer agents. However, despite its potential, there has been limited investigation on the potential anti-cancer agent of DA, especially in breast cancer cells. Therefore, this study aims to investigate the anti-cancer effect of ethanolic extract of DA tubers against the MCF-7 cell lines in vitro and in silico. The in vitro study was carried out by cytotoxicity effect using MTT assay. The in silico study examined active ingredients, determined anti-cancer activity, analyzed the protein target, protein-protein interactions, and molecular docking. The study results showed that the high-concentration ethanolic extract of DA tubers exhibited the highest decrease in MCF-7 cell viability with an IC50 value of 50.98 g/mL and can be categorized as a promising anti-cancer agent. As many as 34 active compounds belonging to anthocyanins, saponins, and flavonoids were screened. Active compounds of DA tubers with a violation score < 2 were analyzed for their biological potentials. Ten compounds of DA with the highest potency were selected for docking analysis with the targeted protein EGFR. The in-silico study showed that 21 bioactive compounds contribute to the anti-cancer activity of DA. Chlorogenic acid is the most promising bioactive compound as an anti-cancer since it is the most similar to the anti-cancer drug. Meanwhile, dihydroquercetin has a low binding affinity value, requiring less energy to bind to proteins in cancer signaling indicated that this compound is promising as anti-cancer. This study suggested that the ethanolic extract of DA tubers can be considered an anti-cancer agent against the MCF-7 cell line in vitro by regulating genetic mutations, apoptosis, and cell proliferation.